PRINCIPAL MANAGEMENT STRATEGIES TO ENHANCE TEACHERS' PEDAGOGIC COMPETENCE IN IMPLEMENTING DIFFERENTIATED - Fitriani, Fitriani; Bahri, Saiful; Hastangka, Hastangka (Jurnal As-Salam, 2025)
The quality of education is largely determined by teachers’ pedagogical competence, which can be enhanced through effective leadership. School principals play a critical role in improving teachers' teaching abilities, particularly in the context of differentiated learning, where strategies are tailored to meet diverse student needs. This study aims to analyze the role of school principals in improving teachers’ pedagogical competence, focusing on their managerial efforts related to differentiated learning. Specifically, the research investigates the principal's role in planning, organizing, implementing, and monitoring differentiated learning to foster improved pedagogical skills among teachers. A qualitative research approach was used with a descriptive design. Seven participants were involved: one principal, two supervisors, and five lead teachers. Data were collected through triangulation techniques to ensure reliability. The study examined the principal’s activities related to differentiated learning and their impact on improving teachers' pedagogical competence. The results of the research findings are as follows: (1) The managerial role of school principals plays an important role in improving teacher competence in differentiated learning. Principals effectively use a variety of strategies to manage and improve the quality of teaching, including planning, organizing, implementing, monitoring and evaluation. (2) The principal has established comprehensive planning steps in improving pedagogical competence in the annual Activity Plan (RKT). (3) The principal has set clear standards and success indicators related to differentiated learning, which are listed under the supervision of teachers. The study concludes that school principals play a vital role in improving teachers' pedagogical competence.